Citizen Participation and Digital Governance in Public Sector Accountability - Rhamadhani, Rika Febby; Edeh, Friday Ogbu (Sinergi International Journal of Accounting and Taxation, 2024)
This narrative review explores the dynamics of social accountability within public sector accounting by synthesizing empirical studies and theoretical frameworks across multiple countries. The objective is to identify key drivers and systemic barriers that influence the effectiveness of social accountability mechanisms. Drawing on literature from databases such as Scopus, Google Scholar, and PubMed, the study employs a thematic analysis to examine the roles of public participation, digital governance, cultural norms, fiscal transparency, and regulatory frameworks. Results indicate that public engagement, when supported by digital platforms and inclusive policies, significantly enhances transparency and institutional trust. However, challenges persist, especially in developing countries, where bureaucratic rigidity, limited resources, and misalignment between global standards and local values hinder reform efforts. The discussion underscores the necessity for integrated governance models that emphasize participatory and transparent processes tailored to sociocultural contexts. Key systemic factors such as independent oversight institutions, technological capacity, and ethical leadership emerge as crucial enablers. The findings suggest that strengthening internal institutional capacity, realigning regulatory reforms with societal expectations, and leveraging technology are essential for advancing social accountability. This review calls for further empirical studies to develop adaptive, context-sensitive frameworks that embed social values in public financial reporting. Ultimately, a people-centered, interdisciplinary approach is imperative for transforming public sector governance into a more accountable and transparent system.